Literature Review: Implications of Acceptance and Commitment Therapy (ACT) on Anxiety in Schizophrenic Patients - Sari, Dewi Keumala; Nasution, Siti Zahara; Ginting, Sadar; Pramesona, Bayu Anggileo (Jurnal Kesehatan, 2023)
Schizophrenia often causes emotional disturbances such as anxiety and depression, which are common mental health problems. Third-wave cognitive therapy such as ACT (Acceptance and Commitment Therapy) in treating anxiety disorders, depression, and anxiety is a practical choice. This literature review aims to identify, evaluate, and synthesize the literature on acceptance and commitment therapy and its application to anxiety in patients with schizophrenia. It also integrates knowledge and experience with the medical literature. The method used is a systematic literature review by analyzing several articles using electronic databases, including ProQuest, Google Scholar, and PubMed. The results of ten selected journal articles demonstrate that ACT is effective in reducing symptoms of anxiety and depression. ACT is effective at treating symptoms of anxiety and depression, and ACT is more effective at treating symptoms of depression than any other available treatment.